2021
DOI: 10.1007/s10570-021-04002-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-productive binding of cellobiohydrolase i investigated by surface plasmon resonance spectroscopy

Abstract: Future biorefineries are facing the challenge to separate and depolymerize biopolymers into their building blocks for the production of biofuels and basic molecules as chemical stock. Fungi have evolved lignocellulolytic enzymes to perform this task specifically and efficiently, but a detailed understanding of their heterogeneous reactions is a prerequisite for the optimization of large-scale enzymatic biomass degradation. Here, we investigate the binding of cellulolytic enzymes onto biopolymers by surface pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 98 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…The role of enzyme glycosylation on lignin tolerance of enzymes has been studied less. Recently, it has been reported that deglycosylation of T. reesei Cel7A slightly increases the non-productive adsorption of this cellobiohydrolase to lignin [ 37 ]. Furthermore, by changing the glycosylation pattern of the CBM1 of TrCel7A, preferential adsorption to cellulose over lignin could be increased [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of enzyme glycosylation on lignin tolerance of enzymes has been studied less. Recently, it has been reported that deglycosylation of T. reesei Cel7A slightly increases the non-productive adsorption of this cellobiohydrolase to lignin [ 37 ]. Furthermore, by changing the glycosylation pattern of the CBM1 of TrCel7A, preferential adsorption to cellulose over lignin could be increased [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A common reaction that occurs with hemicellulose is acetylation, the acetyl group can interfere with the cellulase active site. 30 Arabinoxylooligomers, specifically the less substituted ones, show a greater affinity to occupy the active site compared to cellulose itself, for which the hydrolysis of arabinoxylan to xylose and arabinose is recommended. 31 There are different soluble toxins in the hydrolytic medium that can cause enzymatic deactivation or cause enzyme precipitation, one of them corresponds to the generation of compounds during the process, such as phenolic compounds derived from lignin or the generation of acetyl groups previously described, the same glucose production can generate the inhibition of β-glucosidase.…”
Section: Inhibition Of Cellulase Activitymentioning
confidence: 99%
“…Different cellulose preparations, including Avicel or α-cellulose, as well as lignin isolated by different extraction procedures, are commonly used as model substrates to study the adsorption of enzymes on lignocellulosic biomass [33][34][35]. In this study, commercial α cellulose generated by alkali treatment of cotton linters was selected to investigate enzyme localization and distribution by confocal laser scanning microscopy (CLSM) using two different approaches: (i) directly labeled enzymes; or (ii) applying native enzymes and specific conjugated antibodies.…”
Section: Enzyme Adsorption Studies On Defined Substratesmentioning
confidence: 99%